Quantification of eDNA to Map the Distribution of Cold-Water Coral Reefs - Kutti, Tina; Johnsen, Ingrid Askeland; Skaar, Katrine Sandnes; Ray, Jessica Louise; Husa, Vivian; Dahlgren, Thomas G. (Frontiers in Marine Science, 2020)
An effective management of vulnerable marine ecosystems is dependent on thorough knowledge of their location. Multibeam echo-sounders and remotely operated vehicles (ROVs) are currently used to map areas impacted by industrial activities when sensitive and vulnerable species are expected, however surveying large areas using ROVs is slow and expensive. Here, we developed a species-specific eDNA assay targeting a 178 bp fragment in the control region of the mitochondrial DNA of the cold-water coral (CWC) Lophelia pertusa. The aim was to test if concentrations of L. pertusa eDNA in seawater, determined using droplet digital PCR (ddPCR) technology, could be used to rapidly assess the distribution of CWC reefs in a region. Our assay successfully amplified L. pertusa DNA from seawater. In laboratory we documented an exponential decay rate of the targeted DNA fragment and a linear correlation between coral biomass and eDNA concentrations in flow through microcosms. The ability of the method to detect CWC reefs in situ was tested in the fjords south of Bergen, Norway, where such reefs are common. We tested 5 sites with, and 5 sites without, reefs. Lophelia pertusa eDNA was detected in all 10 deep sites examined. However, concentrations were elevated by 5 to 10 times in water sampled off the two large reefs growing on vertical surfaces. Water sampled 10 m above CWC reefs growing on the flat seabed did not produce an equally clear eDNA signal, nor did single CWC colonies growing on vertical surfaces. Our dispersal model used experimentally derived values for L. pertusa eDNA decay and shedding rates in realistic temperature and salinity. Treating the eDNA as a passive particle with no active vertical or horizontal movement, we successfully modelled the dispersal of eDNA from the known CWC reefs in the region and achieved a good fit with measured eDNA concentrations. In all, our study demonstrated a great potential for eDNA measurements as a cost-efficient tool for a rapid screening of the distribution of CWC reefs growing on vertical surfaces (so called wall reefs) that are challenging to detect using traditional mapping techniques.